Penafsiran Ustadz Adi Hidayat terhadap QS. Al-Baqarah Ayat 285–286 di Platform Digital: Analisis Komparatif Perspektif Klasik dan Kontemporer - Lajnah Mudzrika; Rifqatul Husna (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
The development of digital technology has significantly changed the way Quranic interpretations are disseminated and understood, moving from written form to syafahi interpretations disseminated through various social media platforms. This change demands a selective approach and a more contextual approach to interpretation to ensure the Quran's message remains relevant to modern society. This study examines the syafahi interpretation of the closing verses of Surah Al-Baqarah, verses 285–286, delivered by Ustadz Adi Hidayat on YouTube. It also examines the characteristics and style of his preaching from a comparative perspective between classical and contemporary interpretations. The method used is descriptive qualitative, utilizing content analysis techniques for the lecture material. The results show that Ustadz Adi Hidayat's interpretation is integrative, combining textual and spiritual dimensions, emphasizing the verse's primacy as part of prayer. His interpretation maintains continuity with classical interpretations, particularly in its use of narrations, and is closely related to contemporary interpretations in its emphasis on spiritual and psychological aspects. Therefore, this interpretation can strengthen a relevant and up-to-date understanding of the Quran.